Crustal Velocity Models Retrieved from Surface Wave Dispersion Data for Gujarat Region, Western Peninsular India - Vishwa Joshi (Earth Sciences Research Journal, 2019)
The physiographic features of Gujarat state of western India are unique, as they behaved dynamically with several alterations and modifications throughout the geological timescale. It displays a remarkable example of a terrain bestowed with geological, physiographical and climatic diversities. The massive 2001 Bhuj earthquake (M 7.7) over the Kachchh region caused severe damage and devastation to the state of Gujarat and attracted the scientific community of the world to comprehend on its structure and tectonics for future hazard reduction. In the present study, three clusters of wave paths A, B1, and B2 have considered. In each cluster, dispersion data were measured station by station which collectively formed a dispersion data file for a nonlinear inversion through Genetic algorithm. In this way, three crustal velocity models were generated for entire Gujarat. These models are 1) Across Cambay Basin (Path A), 2) Along Saurashtra - Kathiawar Horst (Path B1) and 3) Along Narmada Basin (Path B2), which were formed at different times during the Mesozoic. The average thickness of the crust estimated in the present study for paths A, B1 and B2 are 38.2 km, 36.2 km, and 41.6 km respectively and the estimated S-wave velocity in the lower crust is ~ 3.9 km/s for all the paths. The present study will improve our knowledge about the structure of the seismogenic layer of this active intraplate region